Evaluasi Profil kuman dan Sensitivitas Antibiotik dari Pasien Pneumonia selama Setahun di RSUD. Saiful Anwar Malang - Tantular, Rezki; Jane, Sugiri; Andreas, Santoso; Kristo, Kurniawan; Yusuf, Mustofa; Abdul, Haris (Jurnal Klinik dan Riset Kesehatan, 2022)
Introduction: Pneumonia is an infection of the lungs (alveoli) caused by bacteria, viruses, or fungi Method: Retrospective study conducted in Saiful Anwar Hospital on January - May 2019. Study samples are sputum, bronchoscopy specimen, or pleural fluid from pneumonia patients from the inpatient ward, outpatient care, and intensive care unit. Data was organized by Microsoft Excel 2016. Result: Pneumonia is more frequent in male (58%) than female (42%) with average of age 56-75 years old. Microbial Profile results are the most common isolate of sputum from Inpatient Ward is Klebsiella pneumoniae ss. pneumoniae Piperacillin/Tazobactam sensitive (100% sensitivity); from Outpatient Care is Klebsiella pneumoniae ss. pneumoniae Amikacin sensitive (100% sensitivity); from Intensive Care Unit is Klebsiella pneumoniae ss. pneumoniae Ceftazidim sensitive (100% sensitivity). Conclusion: The most common isolate of bronchoscopy specimen from Outpatient Care is Klebsiella pneumoniae ss. pneumoniae Ertapenem sensitive (100% sensitivity) while from the Intensive Care Unit is Pseudomonas aeruginosa. The most common isolate of pleural fluid from Inpatient Ward is Pseudomonas aeruginosa while from the Intensive Care is Escherichia coli. Antimicrobial drug sensitivity test could not be conducted on the isolate of bronchoscopy specimen from Outpatient Care, pleural fluid from Inpatient Ward as well as Intensive Care Unit because the isolate number is less than 30.